Discovery of the shrimp Pycnocaris chagoae Bruce, 1972 (Decapoda: Caridea: Gnathophyllidae) in the Lakshadweep Archipelago, India - Prakash, Sanjeevi; Babu, Idrees; Gopi, Mohan; Kumar, Thipparamalai Thangappanpillai Ajith; Balasubramanian, Thangavel (Zootaxa, 2011)
The caridean shrimp family Gnathophyllidae currently comprises five genera: Gnathophyllum Latreille, 1819; Gnathophylloides Schmitt, 1933; Pycnocaris Bruce, 1972; Levicaris Bruce, 1973a and Gnathophylleptum d’Udekem d’Acoz, 2001, the last three genera being monotypic (De Grave et al., 2009). The original description of Pycnocaris chagoae Bruce, 1972 was based on a pair of specimens collected in the Chagos Archipelago, central Indian Ocean (Bruce, 1972). Further information on the morphology and colour pattern of P. chagoae as well as its association with the holothurian hosts Holothuria cinerascenes Brandt and Labidodemas rugosum Ludwig was provided by Bruce (1973, 1983). Since the last record by Bruce (1983), no further specimens of P. chagoae have been reported.